Factor IX Gene Analysis In 70 Unrelated Patients with Haemophilia B: Description of 13 New Mutations - Attali, O.; Vinciguerra, C.; Trzeciak, M. C.; Durin, A.; Pernod, G.; Gay, V.; Ménart, C.; Sobas, F.; Dechavanne, M.; Négrier, C. (Thrombosis and Haemostasis, 1999)
Seventy unrelated patients suffering from haemophilia B have been screened for determining the molecular defect and for evaluating the spectrum of factor IX mutations in the Rhône Alpes region in France. Most patients were characterized with respect to factor IX antigen and factor IX coagulant activity. We have used denaturing gradient gel electrophoresis to obtain a full scanning of the whole coding, promoter, and exon flanking sequences of the factor IX gene. This technique enabled us to determine the molecular defect in 68 out of 70 families (97%), and the mutation was further identified in the two last patients with a direct sequencing of the gene. A total of 2 complete gene deletions in patients with antifactor IX inhibitor, 6 small insertions/ deletions and 62 point mutations were found. Two of these nucleotide substitutions (Arg145His and Ala233Thr) were detected in 21 patients (30%) suggesting the existence of a local founder effect. Thirteen mutations were previously undescribed, including 7 missense mutations. The detection of mutations in patients affected with haemophilia B may shed some light in the structure-function relationship of factor IX molecule within the coagulation system.
Keywords: Haemophilia B; factor IX gene; mutations